Kesalahan Penyelesaian Soal Geometri Transformasi Berdasarkan Gaya Belajar: Studi Kasus Mahasiswa Calon Guru Matematika - Eko Sugandi (Universitas Sarjanawiyata Tamansiswa, 2021)
The diversity of student characteristics is one factor in the difference in errors in solving transformation geometry problems. This research was conducted with the aim of identifying the types of errors in solving geometric transformation problems made by prospective mathematics students based on their learning styles. The errors investigated were based on the criteria of the Kastolan procedure which consisted of conceptual errors, procedural errors and technical errors. The research method used is a qualitative method. The subjects used in the study consisted of three students with the most errors for each category of learning style. The data collection technique was performed using test and interview instruments. The results of the study showed that there were two types of errors made by student teachers with visual learning styles, namely conceptual errors and procedural errors. Prospective teachers with auditory learning styles have three types of errors, namely conceptual errors, procedural errors, and technical errors. Prospective student teachers with kinesthetic learning styles have two types of errors, namely conceptual errors and procedural errors. Based on the research results, it is recommended that additional research be conducted to identify the factors behind the similarity of the types of errors made by candidate student teachers with visual learning styles and styles. kinesthetic learning.